Chronic Management during Pandemic COVID-19 from the Perspective Primary Health Care Practitioners - Alhalawi, Zikri; Sutantri, Sutantri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine how chronic care management for the covid-19 pandemic is managed from the point of view of public health by health practitioners. The method of this research is to use a literature review using the Proquest, Pubmed, Science Direct, and Ebsco databases. The results showed that 718 articles and seven met the criteria for inclusion in the author's review. In conclusion, chronic care management during the Covid-19 pandemic from the perspective of primary health practitioners is very influential in how people with chronic diseases can survive and be helped by improving the quality of their care. Keywords: COVID-19, Primary Health Services and Nurses, Management, Chronic Care